If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -6x = 12x + 21 Reorder the terms: 49 + -6x = 21 + 12x Solving 49 + -6x = 21 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 49 + -6x + -12x = 21 + 12x + -12x Combine like terms: -6x + -12x = -18x 49 + -18x = 21 + 12x + -12x Combine like terms: 12x + -12x = 0 49 + -18x = 21 + 0 49 + -18x = 21 Add '-49' to each side of the equation. 49 + -49 + -18x = 21 + -49 Combine like terms: 49 + -49 = 0 0 + -18x = 21 + -49 -18x = 21 + -49 Combine like terms: 21 + -49 = -28 -18x = -28 Divide each side by '-18'. x = 1.555555556 Simplifying x = 1.555555556
| (1+x)=1.015*1.0280 | | (1+x)=1.015*1.280 | | ln(x+6)+ln(2x)=ln(2) | | X^2+16=16 | | 1.1=1.015*1.05419*(1+x) | | 1.07=1.015*(1+x) | | (1+x)=1.023*1.030 | | -16x-5x=12-9x | | (1+x)=1.019*1.03 | | (1+x)=1.028*1.022*1.04 | | 114-6x=2x+18 | | 1.06=1.022*(1+x) | | 1.07=1.03*1.02*(1+x) | | 0.5*x^3+x^2-10*x+12=0 | | 4x+38=11-25 | | 5x+3=7x-13 | | -4p+9+5p=18 | | x*13=559+5 | | -17x-6=7-9x | | 5x+4=24+x | | 3/5= | | 6y-7=-1 | | 9y=15+4y | | 3(y+2)=8y+10 | | -6+9x=6+8x | | -6-9x=6+8x | | -35+-2f+f^2=0 | | 7(8-z)=21 | | 2(2y-3)=4+3(y-2) | | 6y-7=41 | | 1(6a-6)=12(6a-6) | | 8(3x+2)=184 |